Appropriate Child Participation and the Risks of Spiritual Abuse. (July 2016) - Segura-April, Desiree
How can churches empower children-at-risk as 'vulnerable agents of God's mission, ' while also protecting them from potential risks for manipulation, exploitation, or spiritual abuse? What is 'appropriate participation'? What types of manipulation, exploitation, or spiritual abuse might occur in this participation? This essay seeks to define 'appropriate participation' in the church and mission, drawing substantially from Hart's ladder of participation to analyze the participation of children-at-risk as agents of mission. With this as a foundation, spiritual abuse is defined, and a discussion of how this might happen within the realm of child participation in the ministry of the church and mission is presented. Finally, it presents principles and guidelines that the church should consider as they seek to protect children and youth from potential abuse during the process of participating in God's mission.